Symptom Provocation in Specific Phobia Affects the Substance P Neurokinin-1 Receptor System - Michelgård, Åsa; Appel, Lieuwe; Pissiota, Anna; Frans, Örjan; Långström, Bengt; Bergström, Mats; Fredrikson, Mats (Biological psychiatry (1969), 2007)
Animal studies demonstrate that stress and negative affect enhance the release of the neuropeptide substance P (SP), which binds to the neurokinin 1 (NK1) receptor. This positron emission tomography (PET) study evaluated how the activity in the SP-NK1 receptor system in the amygdala was affected by fear provocation in subjects with specific phobia. Sixteen adult women with DSM-IV–defined specific phobia for either snakes or spiders but not both viewed pictures of feared and non-feared animals while being PET-scanned for 60 min with the highly specific NK1 receptor antagonist [ 11C]GR205171 as the labeled PET tracer. The uptake of the labeled NK1 receptor antagonist was significantly reduced in the right amygdala during phobic stimulation. In the left amygdala no significant differences were found between phobic and non-phobic conditions. There was a negative correlation in the right, but not left, amygdala between subjective anxiety ratings and NK1 tracer binding. Fear provocation affects the SP-NK1 receptor system in the right amygdala. This reflects reduced NK1 receptor availability during fear and could mirror an increased release of endogenous substance P.